Enhancing learning experience with interactive content: A pilot study in designing job application skill lesson plans using Moodle H5p - Umi Kalsom, Masrom; Mardiana, Idris; Mir, Kamran; Sureena, Abdullah (ISTES, 2025)
This study aims to enhance the teaching and learning of job application skills through the design and implementation of interactive content using Moodle H5P. The primary objective of the study is to assess the design of H5P content and the methodology of surveys, ensuring the validity and effectiveness of the instrument. The research employs a quantitative approach, by means of survey to explore how well H5P is received by students in an asynchronous learning environment. The participants were the students enrolled in a communication course in a Malaysian public university. The study took place in an online learning environment, providing flexible and accessible learning experiences for students. The expected outcome is to provide evidence-based recommendations for the design and implementation of interactive content in teaching job application skills. The significance of this study lies in its potential to make a significant impact on the teaching and learning of job application skills and contribute to the literature on the effectiveness of technology-enhanced learning in this area. By providing a more comprehensive and structured approach to teaching job application skills, this research seeks to offer a more effective and efficient way of developing these skills through technology-enhanced learning.